Inequalities for J-Hermitian matrices - Bebiano, N. (2005)
Indefinite versions of classical results of Schur, Ky Fan and Rayleigh-Ritz on Hermitian matrices are stated to J-Hermitian matrices, J = Ir [circle plus operator] -In - r, 0 < r < n). Spectral inequalities for the trace of the product of J-Hermitian matrices are presented. The inequalities are obtained in the context of the theory of numerical ranges of linear operators on indefinite inner product spaces.